Disrupted nitric oxide signaling due to GUCY1A3 mutations increases risk for moyamoya disease, achalasia and hypertension. - Wallace, S; Guo, D-C; Regalado, E; Mellor-Crummey, L; Bamshad, M; Nickerson, D A; Dauser, R; Hanchard, N; Marom, R; Martin, E; Berka, V; Sharina, I; et al. (Clin Genet, 2016)
Moyamoya disease (MMD) is a progressive vasculopathy characterized by occlusion of the terminal portion of the internal carotid arteries and its branches, and the formation of compensatory moyamoya collateral vessels. Homozygous mutations in GUCY1A3 have been reported as a cause of MMD and achalasia. Probands (n = 96) from unrelated families underwent sequencing of GUCY1A3. Functional studies were performed to confirm the pathogenicity of identified GUCY1A3 variants. Two affected individuals from the unrelated families were found to have compound heterozygous mutations in GUCY1A3. MM041 was diagnosed with achalasia at 4 years of age, hypertension and MMD at 18 years of age. MM149 was diagnosed with MMD and hypertension at the age of 20 months. Both individuals carry one allele that is predicted to lead to haploinsufficiency and a second allele that is predicted to produce a mutated protein. Biochemical studies of one of these alleles, GUCY1A3 Cys517Tyr, showed that the mutant protein (a subunit of soluble guanylate cyclase) has a significantly blunted signaling response with exposure to nitric oxide (NO). GUCY1A3 missense and haploinsufficiency mutations disrupt NO signaling leading to MMD and hypertension, with or without achalasia.
Keywords: Adolescent; Adult; Animals; Child; Child, Preschool; Cohort Studies; Esophageal Achalasia; Female; Humans; Hypertension; Infant; Male; Middle Aged; Moyamoya Disease; Mutation; Nitric Oxide; Nonlinear Dynamics; Regression Analysis; Sf9 Cells; Signal Transduction; Soluble Guanylyl Cyclase

Pathogenic FBN1 variants in familial thoracic aortic aneurysms and dissections. - Regalado, E S; Guo, D C; Santos-Cortez, R L P; Hostetler, E; Bensend, T A; Pannu, H; Estrera, A; Safi, H; Mitchell, A L; Evans, J P; Leal, S M; Bamshad, M; et al. (Clin Genet, 2016)
Marfan syndrome (MFS) due to mutations in FBN1 is a known cause of thoracic aortic aneurysms and acute aortic dissections (TAAD) associated with pleiotropic manifestations. Genetic predisposition to TAAD can also be inherited in families in the absence of syndromic features, termed familial TAAD (FTAAD), and several causative genes have been identified to date. FBN1 mutations can also be identified in FTAAD families, but the frequency of these mutations has not been established. We performed exome sequencing of 183 FTAAD families and identified pathogenic FBN1 variants in five (2.7%) of these families. We also identified eight additional FBN1 rare variants that could not be unequivocally classified as disease-causing in six families. FBN1 sequencing should be considered in individuals with FTAAD even without significant systemic features of MFS.
Keywords: Adult; Aged; Aneurysm, Dissecting; Aortic Aneurysm, Thoracic; Exome; Family Health; Female; Fibrillin-1; Genetic Predisposition to Disease; Humans; Male; Marfan Syndrome; Middle Aged; Mutation; Pedigree; Sequence Analysis, DNA